MODERASI BERAGAMA MELALUI PENDIDIKAN ISLAM: INTERNALISASI TOLERANSI DAN PERSAUDARAAN DI ANTARA SISWA GENERASI Z - Surayya, Ely; Ekafitrianda, J.M.; Nasir, Nasir; Husarida, Husarida (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
This study aims to analyze the internalization of religious moderation through Islamic Religious Education (PAI) among Gen Z students at UIN Jambi by examining Qur’anic values on tolerance and Islamic brotherhood (ukhuwah Islamiyah) in the context of the social media era. The research employed a descriptive qualitative method with a literature review and field observation approach. The results indicate that PAI plays a strategic role in instilling religious moderation by integrating Qur’anic values such as Surah Al-Hujurat verse 10 on Islamic brotherhood and Surah Al-Kafirun verse 6 on tolerance. This internalization is carried out through dialogical learning methods, thematic tafsir studies, and discussion practices based on contemporary social media issues. Gen Z students are able to develop tolerant attitudes, respect differences, and strengthen brotherhood in digital interactions. The study concludes that the internalization of religious moderation through Qur’anic-based PAI is effective in shaping students’ inclusive religious character in the social media era.